Phytochemical content and antioxidant activity of einkorn (Triticum monococcum ssp. monococcum), bread (Triticum aestivum L.), and durum (Triticum durum Desf.) wheat - Şahin, Yunus; Yıldırım, Arzu; Yücesan Buhara; Zencirci, Nusret; Erbayram, Şerafettin; Gürel Ekrem (Progress in Nutrition, 2018)
Introduction. Wheat (Triticum ssp.), a major cereal, and its marginally grown hulled ancestor einkorn (Triticum monococcum ssp. monococcum), have bioactive compounds reducing and preventing chronic diseases such as diabetes, cancer, and cardio vascular diseases, besides highly desired nutritional properties. Methods. We evaluated the total phenolics and flavonoids and quantified their phenolic acids, α-tocopherol by high performance liquid chromatography, and their 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. Results. Ferulic acid (148.67-764.04 µg/g), p-coumaric acid (5.06-54.09 µg/g), and total phelonic content (2.06-8.11 µmol GAE/g) of einkorn were significantly higher than bread and durum wheat (p<0.05). Conclusion. Results suggested that einkorn is a rich gene resource for the improvement of modern healthier wheat cultivars.